Development of yogurt-like product from red rice (Oryza sativa) milk. - Tengco, Jan Renzel Lorenzo
Despite the demand for milk consumption is expected to increase abruptly in the following year, certain problems rise upon its consumption as incidences of lactose intolerance and cow-milk allergy have been reported. These circumstances have created avenues for research and development of cost-effective non-dairy substitutes. Hence, this study was conducted to develop a non-dairy, yogurt-like product from red rice and white rice milk ratio. Four formulations, namely F1 (25% red rice, 75% white rice), F2 (50% red rice, 50% white rice), F3 (75% red rice, 25% white rice) and F4 (100% red rice, 0% white rice) were subjected to Preference Ranking Test to determine the most preferred formulation (MPF). The results showed the most preferred formulation was F1 with no significant difference (P>0.05) observed among the 4 formulations using Kramer?s Rank Sum Test. The MPF was then subjected to physico-chemical tests and sensory evaluation tests for charcterization. Using One-Way ANOVA, significant differences (P<0.05) were observed from the means of % titratable acidity, pH, TSS, viscocity and % total ash among MPF and 2 control formulations, namely − Control (0% red rice, 100% white rice) and + Control (100% red rice, 0% white rice). No significant difference was observed on % crude fat of the test formulations. For the anthocyanin content, Fisher?s Least Significant Difference (LSD) revealed that the raw red rice yielded significantly higher (P<0.05) compared with 3 yogurt formulations suggesting that the processing of yogurt massively reduced the pigments in red rice. Ultimately, it was concluded that increasing the amount of red rice in yogurt would also result to higher nutritional value in terms of % crude fat content, % total ash content and anthocyanin content at the expense of its physical properties, as reflected by % titratable acidity, pH, TSS and viscocity. General acceptability test revealed that the MPF had an acceptability of like moderately. Descriptive analysis also revealed that the MPF has a favorable yogurt sensorial characteristic. Paired preference tests of MPF confirmed that the MPF was more preferred over-all than the two control (P<0.05). Comparison of the cadmium and lead contents of oysters (Crassostrea lead contents of oysters (Crassostrea iredalei) harbested from Altavas, Aklan and Dumangas, Iloilo Abstract Oysters are nutritious and popular seafood delicacy grown in the waters of Panay Island. However, due to the quality of their growing waters and their feeding habits, they have become a major food safety concern. Oysters absorb and accumulate heavy metals such as cadmium and lead, which can cause illness when ingested. This study was conducted to measure the amount of cadmium and lead in oysters (Crassostrea iredalei) grown in Altavas, Aklan and Dumangas, Iloilo. The oysters were also characterized in terms of moisture content, protein content, and fat content. The oysters from Altavas contained an average of 1.95 mg kg-1 Pb. Meanwhile, the oysters from Dumangas contained an average of 1.95 mg kg-1 Cd and 3.80 mg kg-1 Pb. The oysters sampled were safe for human consumption in terms of Cd 3.80 mg kg-1 Pb. The oysters sampled were safe for human consumption in terms of Cd and Pb concentrations based on the maximum permissible levels established by the Philippines and Hong Kong. However, they exceeded the maximum permissible levels of Singapore, Malaysia, Australia, New Zealand, United States, and the European Union. There were no significant differences (p>0.05 by t-test) in the Cd and Pb concentrations of oysters grown in both locations. In terms of nutritional contents, oysters from Altavas had 84.41% moisture (WB), 34.02% protein (DB), and 1.402% fat (DB), while oysters from Dumangas contained 87.99% moisture (WB), 41.81% protein (DB), and 1.862% fat (DB). Two-sample t-tests at the 95% confidence level showed that the % moisture content of oysters from Dumangas was higher than those from Altavas. However, there were no significant differences (p>0.05 by t-test) in the protein and fat contents of oysters grown in both locations.